2020
DOI: 10.1371/journal.pone.0230898
|View full text |Cite
|
Sign up to set email alerts
|

FDA orphan drug designations for lysosomal storage disorders – a cross-sectional analysis

Abstract: To provide a quantitative clinical-regulatory insight into the status of FDA orphan drug designations for compounds intended to treat lysosomal storage disorders (LSDs). Methods Assessment of the drug pipeline through analysis of the FDA database for orphan drug designations with descriptive and comparative statistics. Results Between 1983 and 2019, 124 orphan drug designations were granted by the FDA for compounds intended to treat 28 lysosomal storage diseases. Orphan drug designations focused on Gaucher dis… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…Hematopoietic stem cell transplantation is being used in MPS I but requires early diagnosis and treatment [ 25 , 27 ]. Future therapies may rely on in vivo genome editing which uses viral vectors to transmit of functional genes [ 28 ]. Animal studies have shown a good safety profile and promising effects on somatic and also behavioral symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Hematopoietic stem cell transplantation is being used in MPS I but requires early diagnosis and treatment [ 25 , 27 ]. Future therapies may rely on in vivo genome editing which uses viral vectors to transmit of functional genes [ 28 ]. Animal studies have shown a good safety profile and promising effects on somatic and also behavioral symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…ERT is possible due to the cell uptake of mannosylated enzymes via specialized mannose receptors [ 95 ]. Currently, ERT has been approved for Gaucher, Fabry, and Pompe diseases, late infantile neuronal ceroid lipofuscinosis type II, acid lipase deficiency, alpha-mannosidosis, and MPS type I, II, IVA, VI, and VII [ 96 ].…”
Section: Current Proposals For the Treatment Of Gm2 Gangliosidosesmentioning
confidence: 99%
“…In reality, no ERT is yet available that can cross the BBB to treat the primary CNS burden in the majority of LSDs (reviewed in [ 8 ]). CLN2 was the first and only LSD with an approved therapy directly targeted to the brain; all the other therapies address systemic non-neurological manifestations [ 44 ]. Still, even the successful CLN2 brain-targeted ERT is ICV administered, thus circumventing the inability of systemically administered recombinant enzymes to cross the BBB.…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%
“…Their mechanisms of action target the facilitation of subcellular transport [e.g., cysteamine (Cystagon ® ) for cystinosis] and the reduction of storage (miglustat (Zavesca ® ) and eliglustat (Cerdelga ® ), both approved for the treatment of GD). In 2018, the first pharmacological chaperone for an LSD has also reached the market: migalastat (Galafold ® ), which stabilizes misfolded forms of the enzyme alpha-galactosidase A, got FDA approval for the treatment of adults with confirmed FD and an amenable GLA variant [ 44 ].…”
Section: Lysosomal Storage Disordersmentioning
confidence: 99%